Chemical Synthesis of UDP-GlcpA from N-Acetyl Chondrosine and UDP-[β-D-Gal-(1→4)-α-D-Glu] from Lactose - H.A.M. Hassan, Hammed (Asian Journal of Chemistry, 2010)
Further studies on the chemistry of the natural chondrosine as starting material are presented in this paper. Acetylation reactions of either 2-NHAc-3 or 2-NPhth-3 furnished the corresponding peracetylated α-anomer as a sole product in a moderate to fair yields, respectively. Direct MacDonald phosphorylation attempt of acetylated chondrosine ester 4a followed by in situ coupling with uridine-5-monophosphomorpholidate led to isolation of UDP-GlcpA 12 (32 %, 1:1 α/β) among other unreacted phosphates. The expected UDP-chondrosine 11 was not formed as indicated by MS analysis of the crude product. The decomposition of the oxazolidine intermediate 4c under such conditions might account for the failure of preparing 11 in agreement with some literature methods that even used milder phosphorylating agents to add phosphate to carbohydrate-derived oxazolines. For comparison reasons, conducting the same reactions on lactose octaacetate 13 proved to be feasible and gave the corresponding UDP-Lac 16 in good yield and purity. Direct chemical synthesis of the nucleotide 16 represents a simple pathway that is added to the reported enzymatic procedure for finding oligosacc-haride transferases.